Prevention of blood return after indwelling needle placement in a gangrene patient (1例脱疽患者留置针置入后预防回血的护理体会) - ZHENG Jiaqi (郑佳琪); ZHI Hui (智慧); LIU Jinjing (刘津京); CHEN Tao (陈涛) (中西医结合护理)
This paper summarized the prevention of blood return after indwelling needle placement and related nursing for a gangrene patient. Key issues of prevention and nursing included risk factors assessment, standard process, selection of proper puncture sites, tube-sealing method, selection of tube-sealing solution and health education. It is considered that taking effective preventive measures can reduce the occurrence of blood return after indwelling needle and improve the clinical therapeutic effect of indwelling needle. (本文总结1例外脱疽患者留置针置入后预防回血的护理经验, 包括风险因素评估、规范操作、选用合适的穿刺部位、封管方法、封管液的选择以及健康宣教等预防措施。通过科学的预防措施, 有效避免留置针置后的回血现象, 提高留置针临床的治疗效果。)